Data-Driven Interarea Oscillation Analysis for a 100% IBR-Penetrated Power Grid - Miao Zhang; Zhixin Miao; Lingling Fan; Shahil Shah (IEEE Open Access Journal of Power and Energy, 2023)
In this research, a 100% inverter-based resource (IBR)-penetrated bulk power system (BPS) is examined for possible interarea oscillations. A testbed of a BPS constructed in PSCAD, with both grid-forming inverter (GFM)-based IBRs and grid-following inverter (GFL)-based IBRs, is utilized for simulation. For linear analysis, a data-driven method is used to obtain the $dq$ admittance models of the IBRs. This information, combined with our knowledge of the network admittance, leads to eigenvalue analysis of the power grid. Furthermore, for the dominant 3-Hz mode, extended frequency-domain mode shape analysis, along with subgroup effect analysis, and network decomposition analysis are conducted. The analysis results can precisely tell the influencing factors of the oscillation mode. This mode is identified as an interarea oscillation mode. It has a different characteristics compared to the traditional electromechanical interarea mode. Specifically, the network decomposition analysis provides new insights on interarea oscillation modes. The analysis results are all confirmed by the electromagnetic transient (EMT) simulation results.